RFID systems for the control of large inventories (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2014)
The development of new consumption needs certain products from global population growth, this has led to the implementation of technologies that were not taken into account for the improvement of processes involving the control of large inventories within different industries. This work aims to demonstrate the basic operation of radio frequency identification systems (RFID) and the characteristics that affect their use for the control of large inventories. Also, there is a brief description of RFID technology and its components.
Keywords: Tags; inventory logistics; radio frequency identification; systems